PENGARUH KOMPETENSI DAN INDEPENDENSI TERHADAP KUALITAS AUDIT DENGAN PENGALAMAN KERJA SEBAGAI VARIABEL MODERASI PADA KANTOR AKUNTAN PUBLIK(STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK KORWIL SUMATERA BAGIAN TENGAH) - dehilmus, Irwan; Anisma, Yuenita; Hasan, Mudrika Alamsyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to determine the effect of competence and independence on audit quality with work experience as moderating variables. The population in this study is all auditors independence who work in Public Accounting Firm (KAP) Sumatran regional coordinator of the central part as many as 21 KAP. Samples were selected by porpusive sampling techniquewith certain criteria KAP which in Pekanbaru, Padang, Batam, and Jambi city, which sample resulted 75 respondents. The results of study showed that only competence affected audit quality. Independence affected audit quality. Work Experience as moderate affected the relationship of competence and audit quality as well as the relationship of independence and audit quality.Keywords : Competence, Independence, Work Experience, Quality Audit